Factors That Affect the Financial Performance of the Manufacturing Companies Listed on The Indonesia Stock Exchange - Siti Nurlaela, Evia Kurniawati, Kartika Hendra Titiari & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study examined the influence of Current Ratio, Debt To Equity Ratio, andTotal Asset Turnover against the financial performance of the company stated inthe Return On Assets on the manufacturing companies listed on the indonesia stockexchange. Sample from this research is as much as 84 manufacturing companieslisted on the indonesia stock exchange. Types of data used are secondary data thatcomes from the Indonesia Capital Market Directory (ICMD). Results descriptivestatistics showed that an increase in the companys financial performance, which ifviewed from the perameternya the companys financial performance more doneparameter Current ratio. Based on the correlation analysis shows the CurrentRatio effect significantly to Return On Assets, Debt To Equity Ratio was notsignificant effect against the Return On assets, and Total Asset Turnover effectsignificantly to Return On Assets. Based on regression analysis, we find thatvariable Current Ratio, Debt To Equity Ratio, and Total Asset Turnover effectsignificantly to the financial performance of the company stated in the Return OnAssets.Keywords: Company Financial Performance, Return On Asset, Current Ratio, Debt toEquity Ratio, Total Asset Turnover